1986
DOI: 10.1002/cne.902470102
|View full text |Cite
|
Sign up to set email alerts
|

Location and connections of visual cortical areas in the cat's suprasylvian sulcus

Abstract: The initial aim of the experiments described here was to identify and quantify the cortical and thalamic connections of visual cortical areas located in the vicinity of the suprasylvian sulcus. Inputs to various sites in this region were studied by making small injections of wheat germ agglutinin (conjugated to horseradish peroxidase) at physiologically identified locations. Retrogradely labeled cells were counted in each identifiable area of cortex and in thalamic nuclei. Some injections yielded quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 50 publications
12
120
2
Order By: Relevance
“…The lack of acceleration tuning in PMLS matches results from studies in MT, which failed to find evidence of acceleration tuning (Lisberger and Movshon 1999;Price et al 2005). Given the reciprocal anatomical connections among V1, V2 and PMLS (Norita et al 1996;Sherk 1986) and the fact that motion processing is performed synchronously in these brain areas (Dinse and Kruger 1994;Katsuyama et al 1996;Vajda et al 2000), it is logical that we found little evidence for acceleration tuning in V1 and V2.…”
Section: Speed Tuning But Not Acceleration Tuningsupporting
confidence: 80%
“…The lack of acceleration tuning in PMLS matches results from studies in MT, which failed to find evidence of acceleration tuning (Lisberger and Movshon 1999;Price et al 2005). Given the reciprocal anatomical connections among V1, V2 and PMLS (Norita et al 1996;Sherk 1986) and the fact that motion processing is performed synchronously in these brain areas (Dinse and Kruger 1994;Katsuyama et al 1996;Vajda et al 2000), it is logical that we found little evidence for acceleration tuning in V1 and V2.…”
Section: Speed Tuning But Not Acceleration Tuningsupporting
confidence: 80%
“…For example, Sherk (1986) and Grant and Shipp (1991) consider that PMLS and at least parts of VLS and AMLS belong to a single field, the Clare-Bishop area (Clare and Bishop, 1954;Hubel and Wiesel, 1969), while Symmonds and Rosenquist (1984a) and Palmer et al (1978) consider them distinct areas. Analysis, however, can itself inform this issue, since areas that have the same pattern of connections and, therefore, probably constitute a single functional field, will occupy identical positions in diagrams derived by NMDS.…”
Section: Methodsmentioning
confidence: 99%
“…The feline LS cortex is a complex of extrastriate visual areas (Palmer et al, 1978;Sherk, 1986b;Grant and Shipp, 1991;Sherk and Mulligan, 1993) that exhibit functional similarity with areas MT/MST of primates (Payne, 1993), playing an important role in the processing of complex visual motion information (Rauschecker, 1988;Rudolph and Pasternak, 1996;Akase et al, 1998). LS cortex is relatively high level in the hierarchy of the cat visual system (Scannell et al, 1995).…”
Section: Indexing Termsmentioning
confidence: 99%
“…In the visual system, most studies reporting training-induced recovery of function were conducted following damage to extrastriate visual cortex-lesions of the lateral suprasylvian (LS) visual cortex in cats, e.g. (Rudolph and Pasternak, 1996 Pasternak, 2004) or lesions in areas MT/MST of monkeys (Newsome and Pare, 1988;Rudolph and Pasternak, 1999).The feline LS cortex is a complex of extrastriate visual areas (Palmer et al, 1978;Sherk, 1986b;Grant and Shipp, 1991;Sherk and Mulligan, 1993) that exhibit functional similarity with areas MT/MST of primates (Payne, 1993), playing an important role in the processing of complex visual motion information (Rauschecker, 1988;Rudolph and Pasternak, 1996;Akase et al, 1998). LS cortex is relatively high level in the hierarchy of the cat visual system (Scannell et al, 1995).…”
mentioning
confidence: 99%